Characterization and impact of peat fires on stabilization of tropical lowland peats in Banting, Selangor, Malaysia - Azlan Shah Nerwan Shah; Khairul Azlan Mustapha; Roslan Hashim (Penerbit Universiti Kebangsaan Malaysia, 2020)
Peat soil is a representative material of soil and well known as rich in organic matters, high compressibility, high porosity and low shear strength. During dry seasons, peat lands will lose lots of water and potentially turn into a tinderbox bringing in fires. When peat forest fires happen, it prompts degradation of humic-rich organic matter eventually reduce the stability of peat soil. The impacts of peat fire on peat soil from degraded area in Banting, Selangor, Peninsular Malaysia, were investigated through the field identification, physical and engineering properties through burnt peat site. The Unconfined Compressive Strength (UCS) result shows the burnt peat soil gained in strength that strongly related to the binder and filler dosage, moisture content of peat and curing time. The value of UCS strength increased with the gain of moisture content of peat samples but the strength tends to decrease when the moisture content exceeds certain point. The organic material changed its physical and chemical structure resulting from the fire event, thus, the capability of the soil to hold water particles is reducing and yielded higher UCS strength of cement-peat-stabilization. The most important geotechnical aspects of peat that have effect on stabilization process are natural water content, humification grade, ash content, and pH value. The results also suggested that lateral variation within the peat basin indirectly affects the strength of cement-peat-stabilization. The strength of burnt peat can be considerably improved by stabilization and support the concept of Air Curing Technique.